A radar study of Heights of Tops of Cumulonimbus clouds around New Delhi (MAUSAM, 1963)
A study of the height of Cb tops around Delhi as observed bh the high power 3-cm AN-CPS 9 radar on 311 occassions during the various seasons from August 1960 to March 1962 has been studied for this period. The heights of Cb tops grow beyond 40000 ft during the monsoon season on a large number of occassions whereas during the other seasons the tops are much less. There is a tendency of enhanced Cb activity towards the afternoon in the hot weather period while during other seasons there does not seem to exist any such preferred period.